Serial Verb Constructions in Three Tibetan Languages - Dhakal, Dubi Nanda (Gipan, 2024)
This paper presents a description of the serial verb construction (henceforth SVC) in three Tibetan languages- Gyalsumdo, Nubri and Tsum, spoken in Nepal focusing mainly on two verb constructions. The data is collected with the native speakers in different periods and analysed based on the contemporary literatures of SVC. In three selected languages, they share the same arguments (mainly the subject). Temporal and motion verbs are attested in the final position in an SVC in these languages. All of these languages have a closed set of verbs that appear as V2 in SVC. The ordering of most of the verbs participating in SVC is consistent in their occurrence. The three verb serialization is attested only in Nubri.